2011
DOI: 10.1016/j.chom.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial P1-Type ATPases Mediate Resistance to Zinc Poisoning in Human Macrophages

Abstract: SummaryMycobacterium tuberculosis thrives within macrophages by residing in phagosomes and preventing them from maturing and fusing with lysosomes. A parallel transcriptional survey of intracellular mycobacteria and their host macrophages revealed signatures of heavy metal poisoning. In particular, mycobacterial genes encoding heavy metal efflux P-type ATPases CtpC, CtpG, and CtpV, and host cell metallothioneins and zinc exporter ZnT1, were induced during infection. Consistent with this pattern of gene modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
431
3
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(469 citation statements)
references
References 48 publications
21
431
3
14
Order By: Relevance
“…Macrophages use at least three defence mechanisms to fight engulfed bacteria, i.e. oxidative burst, zinc overload and lysozyme production (Botella et al, 2011;Gordon et al, 1974). As ZntA Ef is proven here to be involved in defending E. faecalis against all three host attacks, we propose that this efflux system is one of the main constituents that enables E. faecalis to endure life inside the host.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages use at least three defence mechanisms to fight engulfed bacteria, i.e. oxidative burst, zinc overload and lysozyme production (Botella et al, 2011;Gordon et al, 1974). As ZntA Ef is proven here to be involved in defending E. faecalis against all three host attacks, we propose that this efflux system is one of the main constituents that enables E. faecalis to endure life inside the host.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages are likely to adapt zinc levels in order to inhibit pathogen growth. A recent study reported that Mycobacterium tuberculosis and E. coli use Ptype ATPases in a strategy to avoid the toxic effects of zinc inside macrophages, in which a burst of free zinc occurs within a few hours following bacterial infection (Botella et al, 2011). The roles of ZntA Ef and EF0759 in E. faecalis survival inside macrophages, and in the resistance of the bacterium to oxidative stress and lysozyme, were thus investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Une implication directe de la lectine dans l'internalisation de particules virales menant à l'infection n'a jamais été rapportée. La mutation de ce motif ne modifie pas, par exemple, l'entrée infectieuse du virus de la dengue [9]. En revanche, bien que le mutant di-leucine puisse capturer VUUK, nous avons montré qu'il n'est pas en mesure d'assurer l'endocytose du virus conduisant à l'infection des cellules.…”
Section: Dc-sign a Receptor For Phlebovirusunclassified
“…[8]. Plus récemment encore, nous avons montré au laboratoire qu'une autre de ces ATPases de type P chez M. tuberculosis, la protéine CtpC, est impliquée dans la résistance des bactéries à des concentrations potentiellement toxiques de zinc, et qu'un mutant inactivé dans le gène ctpC se multiplie mal dans les macrophages, sa virulence est donc atténuée [9]. Nous avons également observé, par microscopie confocale et électronique, que du zinc est libéré dans les macrophages au cours de l'infection par M. tuberculosis, une fraction de ce zinc libre s'accumulant dans le phagosome mycobactérien (Figure 2A).…”
Section: Nouvelleunclassified